The punitive populism in the crimes of sexual violation of minors and its impact on criminal jurisdictional activity - Huerta Molina, John Franck (2021)
The punitive populism is characterized by the popular demand for increased penalties and inflexibility in the normative criminal treatment of the accused (elimination of procedural and penitentiary benefits). This populism has fallen especially and palpably on the crime of the sexual violation of minors. The hardening of the legal and punitive treatment for the mentioned crime is notorious since in 2018 life imprisonment was extended. In addition, we have the prohibition of the application of procedural simplification through early termination or conclusion for crimes against sexual freedom, which degenerates the criminal process, delaying it, in many cases, unnecessarily. Likewise, the establishment of a life sentence eliminates the judge,s discretion for a proportional and reasonable application. But this has not been enough; the population demands harsher penalties such as chemical castration and the death penalty. The legislator has taken such demands and has repeatedly embodied them in bills, including most recently in March 2020. However, the question arises as to whether, if the death penalty is constitutionally accepted for the crimes of rape of minors, the judge will have the determination to apply it, since only applying the penalty of life imprisonment requires a qualified motivation with the unanimous decision of a collegiate court. Beyond that, what would it take to apply the death penalty? Certainly, the effects of punitive populism undermine the principles of criminal law, fundamental rights, as well as the performance of the judge in a constitutional rule of law.